HUMAN RIGHTS: what can media activism and journalism learn together? - BRAIGHI, Antonio Augusto (2018)
The objective of the present work, with an essay perspective, is, in the sense of the possibility of constitution of a concept of media activism – and the contemporary investees who declare themselves affiliated to this front of social intervention – understand what can teach to (tele)journalism in relation to Human Rights. However, consider the binomial of militancy superior to a historically legitimized practice would be not only establish hierarchies based on ideological vectors, but also to believe in its candor when, in fact, mediactivism also has limitations in the field that presents here as a problem. In this sense, what could journalism – and more specifically television practice – teach media activism in relation to human rights? This is what is sought in this article, undertaking more provocations than solutions, in the sense of fostering reflection on a latent issue.